Progressive Decline of Semantic Memory with Preservation of Number Processing and Calculation - H. F. A. Diesfeldt (Behavioural Neurology)
A 75-year-old man with seven years of formal education displayed a syndrome of progressive and severe lexical impairments to word comprehension and production (semantic dementia). While he lost the ability to recognize written arithmetical signs, he could still retrieve the arithmetical facts for addition and subtraction of all number combinations of 1 to 9 and 11 to 19, though his mastery of multiplication tables (2 to 9) was unreliable. Calculation procedures were intact. Over the course of 18 months the components of the calculation system dissolved selectively: arithmetical procedures and number reading were spared, despite increasing damage to the arithmetic fact store. He retained the ability to read the time on analogue clocks. Selective preservation of components of the calculation system in the context of severe language deficits and dementia, supports the independent status of numerical abilities. The dissociation between intact arithmetical procedures and impaired table fact retrieval was paralleled by a dissociation between preserved procedures of phonology and syntax of language and impaired retrieval of content words, suggesting that the core deficit was a degradation of the central semantic store of learned knowledge of both words and arithmetic table facts.